P63RhoGEF regulates auto- and paracrine signaling in cardiac fibroblasts. (November 2015) - Ongherth, Anita; Pasch, Sebastian; Wuertz, Christina M.; Nowak, Karolin; Kittana, Naim; Weis, Cleo A.; Jatho, Aline; Vettel, Christiane; Tiburcy, Malte; Toischer, Karl; Hasenfuss, Gerd; Zimmermann, Wolfram-Hubertus; et al.
Abstract: Cardiac remodeling, a hallmark of heart disease, is associated with intense auto- and paracrine signaling leading to cardiac fibrosis. We hypothesized that the specific mediator of Gq/11 -dependent RhoA activation p63RhoGEF, which is expressed in cardiac fibroblasts, plays a role in the underlying processes. We could show that p63RhoGEF is up-regulated in mouse hearts subjected to transverse aortic constriction (TAC). In an engineered heart muscle model (EHM), p63RhoGEF expression in cardiac fibroblasts increased resting and twitch tensions, and the dominant negative p63ΔN decreased both. In an engineered connective tissue model (ECT), p63RhoGEF increased tissue stiffness and its knockdown as well as p63ΔN reduced stiffness. In 2D cultures of neonatal rat cardiac fibroblasts, p63RhoGEF regulated the angiotensin II (Ang II)-dependent RhoA activation, the activation of the serum response factor, and the expression and secretion of the connective tissue growth factor (CTGF). All these processes were inhibited by the knockdown of p63RhoGEF or by p63ΔN likely based on their negative influence on the actin cytoskeleton. Moreover, we show that p63RhoGEF also regulates CTGF in engineered tissues and correlates with it in the TAC model. Finally, confocal studies revealed a closely related localization of p63RhoGEF and CTGF in the trans-Golgi network. Graphical abstract: Schematic overview of signal cascades involved in CTGF expression and secretion in cardiac fibroblasts Angiotensin II (Ang II), Angiotensin II receptor Type 1 (AT1 R), connective tissue growth factor (CTGF), Rho-associated kinase (ROCK), serum response factor (SRF), myocardin-related transcription factor (MRTF), protein kinase N (PKN), and guanine nucleotide exchange factor (GEF). Highlights: p63RhoGEF localizes adjacent to cellular organelles involved in secretion in cardiac fibroblasts. The Ang II-p63RhoGEF-RhoA-actin-MRTF/SRF pathway regulates CTGF in cardiac fibroblasts. p63RhoGEF regulates the biomechanical properties of engineered cardiac tissues.